The Analysis and the Solution of Incubation Period in a Disease Model - Reuben, Anongo Niongon; Hickson, Sikari; O., Kulari Tanzamado; Tirah, Galaya; Atinga, Atimi; Kwala, Alvary K. (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
This study deals with the analysis and the solution of incubation period in a disease model by adopting the mathematical model with incubation period of diseases and the mathematical model without the incubation period of diseases. In the model equations, we partitioned the population into Susceptible (S), Incubated (I), Infected (D) population. We have compared the model equations without incubation period with the model equation with incubation period by solving and incorporating the system of first order linear equations into fourth order Runge-kutta method which has better error accuracy for solving first order equations. Graphical results for incubation class show that the infectious diseases were fatal if immediate attention is not given to endemic villages and communities.Keywords: SID Model, Incubation period, Runge-kutta method, numerical simulation, transmission.